2021
DOI: 10.1002/smll.202101881
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite‐Free Li Metal Anodes and the Formation of Plating Textures with a High Transference Number Modified Separator

Abstract: The application of Li metal anodes is currently hindered by the uncontrolled growth of Li dendrites. Herein, the effects of a modified separator with a high Li+ transference number (t+) on the structure and electrochemical performance of Li metal anodes are reported. Stable and dendrite‐free plating/stripping cycles are achieved under current densities up to 5 mA cm−2 and areal capacities up to 20 mAh cm−2. The uniformly grown Li grains under the high t+ environment also exhibit well‐defined textures (preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…With the improvement of human production efficiency and the acceleration of the pace of life, the charging energy storage equipment is widely used in various industries, and human demand for the charging mobile energy storage equipment is getting higher and higher. In the past few decades, lithium-ion batteries have become more and more popular because of their high safety performance, charging efficiency, and energy density. However, due to the increasing demand for energy storage equipment, lithium–sulfur batteries (LSBs) with higher energy density and lower production cost have attracted wide attention. LSBs have many advantages, including high energy density (2600 Wh kg –1 ), wide operating temperature (−30 to 60 °C), and lower electrode material cost, but the disadvantages of LSBs are also obvious. First of all, the electronic conductivity of sulfur is very poor (5 × 10 –30 S cm –1 ), which results in the low utilization rate and poor dynamic performance for the active material .…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of human production efficiency and the acceleration of the pace of life, the charging energy storage equipment is widely used in various industries, and human demand for the charging mobile energy storage equipment is getting higher and higher. In the past few decades, lithium-ion batteries have become more and more popular because of their high safety performance, charging efficiency, and energy density. However, due to the increasing demand for energy storage equipment, lithium–sulfur batteries (LSBs) with higher energy density and lower production cost have attracted wide attention. LSBs have many advantages, including high energy density (2600 Wh kg –1 ), wide operating temperature (−30 to 60 °C), and lower electrode material cost, but the disadvantages of LSBs are also obvious. First of all, the electronic conductivity of sulfur is very poor (5 × 10 –30 S cm –1 ), which results in the low utilization rate and poor dynamic performance for the active material .…”
Section: Introductionmentioning
confidence: 99%
“…[195] The modified separator with a high Li-ion transfer number contributes to the preferred orientations of Li deposition with well-defined textures, and endows stable columnar Li plating to a high capacity of 20 mAh cm −2 . [196] The coating layer on the routine separator can also change the mechanical performance and regulate the Li depositing behaviors. [199] Li et al reported the inhibition of Li dendrite growth by coating a thin layer of ultra-strong diamond-like carbon (DLC) on polypropylene (PP) separators.…”
Section: Modification Of Separatorsmentioning
confidence: 99%
“…[ 195 ] The modified separator with a high Li‐ion transfer number contributes to the preferred orientations of Li deposition with well‐defined textures, and endows stable columnar Li plating to a high capacity of 20 mAh cm −2 . [ 196 ]…”
Section: Regulation Strategiesmentioning
confidence: 99%
“…To extend the cycling life of LMAs, ongoing efforts have been made to regulate the Li deposition/dissolution behavior for stable Li metal anodes, including (i) electrolyte optimization, 20–23 (ii) introduction of the artificial solid electrolyte interphase, 24–30 (iii) separator engineering, 31–33 and (iv) anode structure modifications 34–43 . Among them, the anode structure modifications, including Li metal reconstitution and the employment of porous current collectors, demonstrate excellent efficiency in inhibiting Li metal dendrite growth and buffering Li metal volume fluctuation changes 34,35,40,44–48 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] However, Li metal anodes (LMAs) suffer from an uncontrollable growth of Li dendrites and volume expansion of Li metals, which significantly restricts the commercialization step to the practical applications. [16][17][18][19] To extend the cycling life of LMAs, ongoing efforts have been made to regulate the Li deposition/dissolution behavior for stable Li metal anodes, including (i) electrolyte optimization, [20][21][22][23] (ii) introduction of the artificial solid electrolyte interphase, [24][25][26][27][28][29][30] (iii) separator engineering, [31][32][33] and (iv) anode structure modifications. [34][35][36][37][38][39][40][41][42][43] Among them, the anode structure modifications, including Li metal reconstitution and the employment of porous current collectors, demonstrate excellent efficiency in inhibiting Li metal dendrite growth and buffering Li metal volume fluctuation changes.…”
Section: Introductionmentioning
confidence: 99%